PENGARUH STRATEGI PEMBELAJARAN CRITICAL INCIDENT DALAM MENINGKATKAN KEMAMPUAN MENULIS PUISI BERDASARKAN UNSUR INTRINSIK DAN EKSTRINSIK PADA KELAS VIII SMP NEGERI 1 POLEWALI - Abdul Muttalib; Wahyuddin Wahyuddin; Nur Hafsah Yunus (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2020)
The aim of this research is to describe the influence of critical incident learning strategies in improving the ability to write poetry in deep structure and surface structure of Class VIII SMP Negeri 1 Polewali Mandar. This research is categorized into experimental research, namely quasi-experimental research (quasi-experimental design). The results of data analysis before implementing the critical incident learning strategy in the Experiment class, the average value of learning outcomes written in poetry was 1.93, and experienced a significant increase after the implementation of critical incident learning strategies by obtaining an average value of learning outcomes for the ability to write poetry of 2 , 75. This is inversely proportional to the Control class which applies conventional learning strategies with the acquisition of an average value, before the action given is 1.97 and has a less significant increase than the Experiment class, which is 2.17. Hypothesis test results that show the sig (2-tailed) value of 0.0001 <0.05 and the value of t_hitung on equal variances is assumed to be = 4.331 df = 57 and so that tcount is 4.331> ttable = 2.04, so based on the independent sample t test above it can be denied that it is accepted; H1, the application of learning strategies that affect the ability to write poetry in VIII grade students of SMP Negeri 1 Polewal